Differential Effect of Visual and Proprioceptive Stimulation on Corticospinal Output for Reciprocal Muscles - Suzuki, Takako; Suzuki, Makoto; Kanemura, Naohiko; Hamaguchi, Toyohiro (Frontiers in Integrative Neuroscience, 2019)
This study investigated the corticospinal excitability of reciprocal muscles during tasks involving sensory difference between proprioceptive and visual inputs. Participants were instructed to relax their muscles and to observe a screen during vibratory stimulation. A video screen was placed on the board covering the right hand and forearm. Participants were randomly tested in four conditions: resting, control, static, and dynamic. The resting condition involved showing a black screen, the control condition, a mosaic patterned static videoclip; the static condition, a static videoclip of wrist flexion 0º; and the dynamic condition, a videoclip that corresponded to each participant’s closely-matched illusory wrist flexion angle and speed by vibration. Vibratory stimulation (frequency 80 Hz and duration 4 s) was applied to the distal tendon of the dominant right extensor carpi radialis (ECR) using a tendon vibrator in the control, static, and dynamic conditions. Four seconds after the vibratory stimulation (end of vibration), the primary motor cortex at the midpoint between the centers of gravity of the flexor carpi radialis (FCR) and ECR muscles was stimulated by transcranial magnetic stimulation. The ECR motor evoked potential (MEP) amplitudes significantly increased in the control condition compared to the resting condition, whereas the FCR MEP amplitudes did not change between the resting and control conditions. In addition, the ECR MEP amplitudes significantly increased in the static condition compared to the dynamic condition. However, the FCR MEP amplitudes significantly increased in the dynamic condition compared to the static condition. These results imply that the difference between visuo-proprioceptive information had an effect on corticospinal excitability for the muscle. In conclusion, we found that proprioceptive and visual information differentially altered the corticospinal excitability of reciprocal muscles.